2020
DOI: 10.1109/access.2020.2988529
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Inspired Navigation Strategy Fused Polarized Skylight and Starlight for Unmanned Aerial Vehicles

Abstract: The migratory animals are capable of traveling long distances by fusing varied information, such as the halteres, the star positions, and the polarization pattern. Motivated by the navigation strategy of migratory animals, a bio-inspired navigation strategy based on polarized skylight, starlight, and halteres is presented in this paper. To enhance the environmental adaptability of the polarization navigation system, a sun vector calculation method tightly fusing the degree of polarization (DoP) and the azimuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The logarithm amplification gives the ability to deal with a large range of lighting conditions over several decades. Thus, it becomes possible to make an array of POL units distributed on a planar surface [ 236 ] along a circular [ 167 , 237 , 238 ] or even spherical shape mimicking a compound eye [ 239 , 240 , 241 ]. Moreover, a spherical sensor composed of several POL units was used to compensate for the error alignments of an inertial measurement unit on the basis of sun and star vectors [ 241 ].…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The logarithm amplification gives the ability to deal with a large range of lighting conditions over several decades. Thus, it becomes possible to make an array of POL units distributed on a planar surface [ 236 ] along a circular [ 167 , 237 , 238 ] or even spherical shape mimicking a compound eye [ 239 , 240 , 241 ]. Moreover, a spherical sensor composed of several POL units was used to compensate for the error alignments of an inertial measurement unit on the basis of sun and star vectors [ 241 ].…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
“…As far as we know, only PbCs have been combined with Integrated Navigation Systems (INS). They could be either based on a PbC/INS with a heading accuracy ranging from 0.08° to 0.8° in sunny weather, but 0.8° to 1.5° in cloudy conditions [ 179 , 240 , 241 , 243 , 244 , 245 , 246 ], or PbC/GNSS/INS with a heading accuracy ranging from 0.02° to 6.5° [ 175 , 247 , 248 , 249 ], or PbC/SLAM/INS with a heading accuracy from 0.28° to 4.7° and a geographical position error from 1.96 m to 8.7 m [ 214 , 250 , 251 , 252 , 253 ]. The heading and trajectory accuracy can therefore be improved by about 40% compared to conventional navigation systems in complex outdoor environments [ 22 ].…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
“…Celestial objects, such as stars and the sun have continued to play an important role in land-based, maritime, and aerospace navigation [18][19][20][21][22][23][24]. Not only the information directly from the celestial object but also the celestial information like the polarised light from the sun or the moon can be used as an orientation cue in many navigation approaches and applications [25,26]. Some recent works have also achieved angle determination utilizing celestial information under low-light conditions that were inspired by biological navigation mechanisms; for example, one approach utilises a biomimetic polarisation sensor coupled with a fisheye lens to achieve night heading determination [27].…”
Section: The Celestial Compassesmentioning
confidence: 99%
“…Guo et al used 9 polarized light sensors distributed in a hemisphere to assist with starlight and inertial information and developed an integrated navigation system which can work normally even when only one star is observed during the day. The simulation results showed that it realized the accuracy of 0.02° [26]. The existing combination solutions work with large instrument mass and volume, but limited orientation measurement accuracy.…”
Section: Introductionmentioning
confidence: 96%
“…All-day star sensors[19],[35] All-day navigation, big size and mass high accuracy of several arcseconds Hemispherical sun sensor array[21] Daytime navigation only 0.2°× 0.1° Polarized light sensor[26] …”
mentioning
confidence: 99%